Highly Efficient Biosynthesis of Glycyrrhetinic Acid Glucosides by Coupling of Microbial Glycosyltransferase to Plant Sucrose Synthase - Ali, Mohamed Yassin; Chang, Qing; Yan, Quande; Qian, Zheng; Guo, Xiang; Thow, Kieran; Wu, Jinhong; Zhang, Yong; Feng, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Glycyrrhetinic acid (GA) glycoside derivatives are important bioactive pentacyclic triterpenoid compounds. Glycyrrhetinic acid is the most important Glycyrrhiza uralensis component due to its potent anti-inflammatory activity and extensive use in the pharmaceutical and cosmetics industries. UDP-glycosyltransferases (UGTs) catalyze various natural products' glycosylation using Glycyrrhetinic acid (GA) is a principal bioactive pentacyclic triterpenoid from Glycyrrhiza uralensis. UDP-dependent glycosyltransferases (UGTs) have been widely used to catalyze glycosylation of diverse nature products for developing potential therapeutic compounds. In this study, we have characterized a UGT109A3 from Bacillus subtilis, which can glycosylate both the free C3 hydroxyl and C30 carboxyl groups of GA to yield a unique 3, 30-O-β-D-diglucoside-GA. By coupling the microbial UGT109A3 to plant sucrose synthase (SUS), GA-diglucoside could be biosynthesized in an efﬁcient and economical way. With a fed-batch glycosylation, a large scale of GA-glucoside (4.98 g/L, 6.26 mM in 8 hours) could be enzymatically transformed from GA. The obtained GA-diglucoside showed a significant water solubility improvement around 3.4×103 fold compared with that of the parent GA (29 µM). Moreover, it also exhibited dose-dependent cytotoxic towards human colon carcinoma Caco-2 cell line according to MTT assay, having an IC50 at 160 µM. This study not only builds up an efficient platform for producing GA-glucosides, and also is valuable for further biosynthesis of other complex glycosylated natural products.